2010
DOI: 10.1007/s00586-010-1628-y
|View full text |Cite
|
Sign up to set email alerts
|

Delayed presentation and diagnosis of cervical spine injuries in long-standing ankylosing spondylitis

Abstract: Patients with ankylosing spondylitis (AS) are vulnerable to cervical spine fractures. Long-standing pain may mask the symptoms of the fracture. Radiological imaging of the cervical spine may fail to identify the fracture due to the distorted anatomy, ossified ligaments and artefacts leading to delay in diagnosis and increased risk of neurological complications. The objectives are to identify the incidence and risk factors for delay in presentation of cervical spine fractures in patients with AS. Retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 19 publications
2
42
0
2
Order By: Relevance
“…Standard imaging is not always helpful in diagnosing spine fractures in AS patients. Spine radiographs with their two-dimensional approach are often difficult to read given the distorted anatomy resulting from a kyphotic spine (8,9). Some emphasize the advantage of MRI over CT given that it is more sensitive at detecting soft tissue abnormalities and neurologic manifestations such as spinal cord damage (10).…”
Section: Introductionmentioning
confidence: 99%
“…Standard imaging is not always helpful in diagnosing spine fractures in AS patients. Spine radiographs with their two-dimensional approach are often difficult to read given the distorted anatomy resulting from a kyphotic spine (8,9). Some emphasize the advantage of MRI over CT given that it is more sensitive at detecting soft tissue abnormalities and neurologic manifestations such as spinal cord damage (10).…”
Section: Introductionmentioning
confidence: 99%
“…The study by Anwar et al [3] in the March issue is a good reminder of the difficulty in detecting cervical spine injuries in long-standing ankylosing spondylitis. The authors retrospectively report a case series of 32 patients with AS and cervical fractures.…”
Section: Ankylosing Spondylitismentioning
confidence: 99%
“…8 The annulus fibrosus is a fibrous ring that surrounds the central portion of the intervertebral disc known as the nucleus pulposus. Ossification of the spinal ligaments and calcification of the annulus fibrosus result in a rigid spine with a limited ability to absorb even minimal impact.…”
Section: Long Answermentioning
confidence: 99%
“…Indeed, one retrospective review showed that 60% of cervical fracture dislocations were undetectable on initial radiographs. 8 Computed tomography is more sensitive than plain radiography in identifying fractures, with a reported sensitivity of 100% and specificity of 99%. 12 Although plain radiography can identify a fracture, computed tomography and magnetic resonance imaging can better define the character of the fracture.…”
Section: Long Answermentioning
confidence: 99%